Порівняльні дослідження японської міфології в контексті переказів про Сахохіме та Сахохіко - Морі Масако (Народна творчість та етнографія, 2009)
The article is about the history of the comparative research of the Japanese mythology. The similarity of Indo-European and Japanese myths is not casual, but is the result of communications and mutual influence of different people. The similarity of "The Volsunga Saga”, which in opinion of author came to Japan and became firmly established here in the form of narration about Sahohime and Sahohiko, is examined.